In Vitro and In Vivo Osteogenesis Induced by Icariin and Bone Morphogenetic Protein-2: A Dynamic Observation - Xie, Lina; Liu, Ning; Xiao, Ye; Liu, Yanhui; Yan, Chunge; Wang, Gailing; Jing, Xiangdong (Frontiers in Pharmacology, 2020)
In the present study, we aimed to compare the effects of icariin (ICA) and bone morphogenetic protein-2 (BMP-2) on osteoblast proliferation and osteogenesis in bone defects. In Experiment 1, human osteoblasts were cultured in vitro with different concentrations of ICA and BMP-2. Cell proliferation was detected by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), western blot, and quantitative real-time polymerase chain reaction (qPCR) assays. In Experiment 2, 18 New Zealand white rabbits were randomly divided into control, ICA, and BMP-2 groups. Animal models of mandibular defects penetrating the mandible were prepared in all rabbits. The animals were then euthanized at 4, 8, and 12 weeks post-operation. Bone defects and repair were observed using hematoxylin-eosin and Goldner’s trichrome staining techniques. In Experiment 1, MTT and qPCR results showed that 10–40 µg/mL of ICA and 50 µg/mL of BMP-2 could promote osteoblast proliferation and upregulate BMP-2, osteoprotegerin (OPG), and alkaline phosphatase (ALP) mRNAs to varying degrees. Specifically, ICA at concentration of 30 µg/mL and BMP-2 at concentration of 50 µg/mL had the strongest ability to promote cell proliferation. Western blot results indicated that both ICA and BMP-2 could promote the expression of BMP-2 and OPG proteins. In Experiment 2, the animal model of bone defects was successfully prepared. Compared with the control group, higher osteogenesis was observed in the ICA and BMP-2 groups at different observational times. At four weeks post-operation, osteogenesis in the BMP-2 group was slightly higher than that in the ICA group, but there was no significant difference between the two groups until the eighth week. ICA promotes osteoblast proliferation by stimulating the expression of BMP-2 and OPG proteins and upregulating the expression of BMP-2, OPG, and ALP mRNAs. ICA at a certain concentration has the same osteogenic effect as BMP-2. ICA/BMP-2 composite nanomaterials can be used as a framework to guide bone regeneration and promote osteogenesis. In addition, the combined use of hematoxylin-eosin and Goldner’s trichrome staining techniques contributes to acquiring better bone morphometric information about bone defects.